2023
DOI: 10.1002/smll.202208089
|View full text |Cite
|
Sign up to set email alerts
|

3D Printable Gelatin Methacryloyl (GelMA)‐Dextran Aqueous Two‐Phase System with Tunable Pores Structure and Size Enables Physiological Behavior of Embedded Cells In Vitro

Ghazi Ben Messaoud,
Sanja Aveic,
Mattis Wachendoerfer
et al.

Abstract: The restricted porosity of most hydrogels established for in vitro 3D tissue engineering applications limits embedded cells with regard to their physiological spreading, proliferation, and migration behavior. To overcome these confines, porous hydrogels derived from aqueous two‐phase systems (ATPS) are an interesting alternative. However, while developing hydrogels with trapped pores is widespread, the design of bicontinuous hydrogels is still challenging. Herein, an ATPS consisting of photo‐crosslinkable gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…S1, ESI †). 58 We have previously shown that phase separation occurs between pH 5.1 and pH 3.6, therefore above and below the IEP of GelMA, which highlights the influence of the protein charge density on the phase separation process, as shown in (Fig. 2A).…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…S1, ESI †). 58 We have previously shown that phase separation occurs between pH 5.1 and pH 3.6, therefore above and below the IEP of GelMA, which highlights the influence of the protein charge density on the phase separation process, as shown in (Fig. 2A).…”
Section: Resultsmentioning
confidence: 51%
“…During phase inversion, the system consisting of dextran droplets dispersed in the GelMA rich-phase coexists with GelMA droplets dispersed in the dextran phase. 58 Although the origin of the formation of a multiple emulsion is still unknown and is beyond the scope of this work, it could be related to some intrinsic properties of GelMA, near the IEP. For instance, the self-association of the modified gelatin molecules in the absence of charge repulsion may affect the random coil conformation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We note that all GelMA/bPE inks were prepared in Dulbecco’s phosphate-buffered saline (DPBS), maintaining pH = 7.4, which lies within the isoelectric point ( pI ) of native gelatin type A (7 < pI < 9) . While gelatin and GelMA are both polyampholytes containing carboxylic acid and amino groups, the modification of gelatin into GelMA, pursued by methacrylation of the amino and hydroxyl groups on the gelatin backbone, shifts the pI to values approaching 4–5 and changes the availability of ionizable groups. , The pI and charge density of GelMA are, therefore, expected to depend on its degree of functionalization (DoF). Here, a particular concern is whether interactions between charged GelMA (above its pI ) and bPEs lead to the complexation of GelMA with bPE and/or whether GelMA influences the complexation-driven self-assembly of the oppositely charged bPEs, leading to an inhomogeneous microstructure (flocculation and phase separation) within the GelMA/bPE inks.…”
Section: Resultsmentioning
confidence: 99%